Prevalence of adenomas and sessile serrated adenomas in Chinese compared with Caucasians. Issue 4 (25th March 2013) - Kumbhari, Vivek; Behary, Jason; Hui, Jason Minco
Abstract: Background and Aims: Colonic adenomas and sessile serrated adenomas (SSA) are the most common premalignant polyps identified at colonoscopy. This study compares the prevalence of neoplastic polyps in Chinese and Caucasians in a general gastroenterology outpatient practice in Australia. Methods: This study included consecutive unselected colonoscopies performed for standard clinical indications by a single endoscopist (JMH). All polyps detected were measured, resected, and sent for histopathology. The prevalence of adenomas, advanced adenomas, SSA, and cancer in the Chinese and Caucasian cohorts were compared. Advanced adenomas were defined as adenomas > 10 mm, villous histology, or high‐grade dysplasia. Results: The study included 346 Chinese and 654 Caucasians. There was no significant difference in the baseline characteristics including age, gender, and indications of colonoscopy, although Chinese were more likely to present with rectal bleeding (22.8% vs 15.9%, P = 0.01). The prevalence of adenomatous polyps was similar in both Caucasians (34.3%) and Chinese (35.3%). However, advanced adenomas were more significantly common in Caucasians (11.3%) compared with Chinese (4.6%) ( P < 0.001). SSA was rare in Chinese (2%) but present more frequently in Caucasians (7%) ( P = 0.001). Multivariate analysis showed that Caucasian ethnicity (odds ratio 2.4, 95% confidence interval 1.6–3.6) and the presence of SSA (odds ratio 4.4, 95% confidence interval 2.3–8.6) were independent predictors for the detection of an advanced adenoma. Conclusions: The prevalence of significant colorectal lesions, including advanced adenomas, large adenomas, and SSA, were lower in Chinese compared with Caucasians. These findings may influence the guidelines for colonic cancer screening in Chinese populations.